Implementasi Pembelajaran Outdoor Learning dalam Mengembangkan Kecerdasan Naturalis Anak Usia Dini - Atiek Puspita Sari; Deni Febrini; Wiwinda Wiwinda (Journal of Elementary School (JOES), 2023)
This research is a descriptive qualitative research with a naturalistic approach. Data collection methods in the form of observation, interviews and documentation. The subjects of this study were students of RA Misbahul Khair, Bengkulu City, tested the validity of the data by triangulation of sources and techniques, as well as data analysis of the Miles and Huberman models. The results of the study: (1) The implementation of outdoor learning in developing the naturalist intelligence of early childhood RA Misbahul Khair Bengkulu City, on the theme of the Universe was carried out with three activity models, namely first, field trips, this method was carried out with a preparatory step, namely determining activities according to the theme through meetings. teachers and guardians discuss the technical implementation and preparation of funds. Third, the evaluation is carried out at a teacher meeting to find out the successes and obstacles faced. second, the natural exploration activity (JAS) which is carried out in the sub-theme of natural objects is carried out with preparatory steps, namely material preparation (compiling RPPH) and implementation techniques, then the implementation step begins with the opening, namely greetings, praying, dawamul Qur'an and apperception. on the theme of natural objects The three eco-study activities in the sub-theme of natural phenomena are carried out in three steps, namely preparation, preparing RPPH and preparing the required tools. Second, the implementation step includes the opening containing greetings, praying, dawamul Quran, apperception about the sub-themes of natural phenomena. Core activities carried out outside the classroom are taking care of the school garden by pulling grass and watering plants. Closing stage with questions and answers on activities that have been carried out. Third, evaluation by making or filling out daily assessments of child development based on the results of observations and interviews in the eco-study activities. (2) The results of the implementation are shown by the level of achievement of children developing according to expectations (BSH) in several indicators of naturalist intelligence including 3 out of 11 children are able to recognize and mention natural objects, 2 out of 11 children are able to show concern for the environment, 2 out of 11 children like to feed rabbits, 4 out of 11 children are able to take care of plants, and 8 out of 11 children are happy and enthusiastic when learning outside the classroom. (3) supporting factors for outdoor learning include: Adequate infrastructure, competent teachers, strategic geographical location, inhibiting factors including time allocation, weather and a less conducive learning atmosphere. Alternative solutions for inhibiting factors include; Create activity mapping. Keywords: Outdoor Learning, Naturalist Intelligence, Early Childhood